Justice in Plea Bargaining in India : a Review of major drawbacks - Bhardwaj, Dr . Manish (Innovative Research Thoughts, 2018)
A new idea in India, plea bargaining. In today's criminal justice system, most convictions are obtained through plea bargaining. It is the procedure through which the accused and the prosecution in a criminal case work out a mutually acceptable resolution of the case. It generally entails pleading guilty to a lower charge in one or more courts of a multi-count indictment in exchange for a shorter sentence. “As a result, plea-bargaining refers to pre-trial conversations in which the accused agrees to plead guilty in return for a less sentence. India's status is somewhat different. Plea bargaining is a common tactic in the US and Europe to assist speed up the judicial process.